Prevention and treatment of tuberculosis before two great discoveries of the 20th century: the Bacillus Calmette-Guérin vaccine and streptomycin - Adamowicz, Dominik; Łopuszyńska, Inga; Zembala, Julita; Stańczyk, Justyna; Meliksetian, Astrik; Wosińska, Alicja; Pazik, Dorota; Kosecka, Katarzyna; Cieślik, Aleksandra; Jargieło, Anna (Journal of Education, Health and Sport, 2023)
Introduction and Purpose. Fundamental milestone in fight against tuberculosis is the invention of the effective vaccine, but before Anthony van Leeuwenhoek was the first to observe the bacteria, which opened the door to the first vaccinations in the 19th century. Medicine had battled against infectious diseases in different ways. Some methods can be perceived as a kind of primitive vaccines, which couldn’t, however, considerably affect a decrease in the epidemic range, due to their uncommon use and limited effectiveness. The aim of this paper is to analyze the history of tuberculosis and the role of Poland in the fight against it. Materials and methods. PubMed database was used for review of the literature. The following phrases were searched in English: “tuberculosis”, “vaccination”, “BCG vaccine”, “sanatorium”. Description of the state of knowledge. Poland played an important role in the fight against tuberculosis. It was in the laboratory of Polish pharmacist, where Koch discovered its etiological factor. In the territory of Poland there are prototypes of modern sanatoria for tuberculosis patients. Article also presents old and modern methods of tuberculosis treatment, as the use of specific climatic conditions, which resulted in developing health-resort treatment. A breakthrough in the methods used was the discovery of streptomycin in the middle of the 20th century, which led to the development of pharmacological treatment, nowadays involving the administration of proper combinations of drugs. Summary. The increasingly strong anti-vaccine movement is slowly destroying what people have been fighting for the centuries. It is worth recalling how we reached milestones in this fight and why immunization is so important for all societies.